Evaluation of Objective Sedation Monitoring Practices in Critically Ill Adult Patients: A Systematic Review and Meta-Analysis - Natalia Jaworska, MD, MSc; Areej Hezam, MSc; Thérèse Poulin, BHSc; Julie A. Kromm, MD; Lisa D. Burry, PharmD, PhD; Daniel J. Niven, MD, MSc, PhD; Kirsten M. Fiest, PhD (Critical Care Explorations)
OBJECTIVES:. To conduct a systematic review and meta-analysis to determine if objective sedation monitoring practices reduce duration of mechanical ventilation and other clinical and healthcare utilization outcomes in critically ill adult patients. DATA SOURCES:. Ovid MEDLINE, Embase, CINAHL, PsycINFO, Web of Science, Cochrane Library and PROSPERO, and the grey literature. STUDY SELECTION:. Observational or interventional original research studies, conducted in adult critically ill patients undergoing invasive mechanical ventilation, evaluating any objective sedation monitoring practice (e.g., electroencephalography [EEG]), and reporting on duration of mechanical ventilation or other secondary outcomes (e.g., length of stay) were included. DATA EXTRACTION:. Meta-analysis was performed for pooled estimates of the primary outcome and each individual secondary outcome using random-effects modeling. DATA SYNTHESIS:. Twenty studies (3410 patients) were included with 15 studies evaluating processed EEG monitoring, 2 evaluating EEG monitoring, and 3 evaluating processed facial electromyography (EMG). Processed EEG was not associated with reduced duration of mechanical ventilation (standardized mean difference [SMD] –0.33; 95% CI, –0.91 to 0.25; I2 = 84.4%). Secondary outcomes of processed EEG monitoring showed decreased hospital length of stay (days) (SMD –0.89; 95% CI, –1.17 to –0.62; I2 = 13.4%), reduced total sedative dose (reported in propofol equivalents, mg) (SMD –1.29; 95% CI, –2.27 to –0.31; I2 = 96.6%), and reduced total opioid dose (reported in morphine equivalents, mg) (SMD –0.40; 95% CI, –0.76 to –0.04; I2 = 77.0%). Processed facial EMG was associated with an increased risk of adverse events (risk ratio 1.40; 95% CI, 1.03–1.90; I2 = 0.00%). Risk of bias was serious for 65% (n = 13/20) of included studies. CONCLUSIONS:. Processed EEG monitoring is not associated with reduced duration of mechanical ventilation but may be associated with reduced sedative and opioid exposure and decreased hospital length of stay. Processed facial EMG monitoring may be associated with increased adverse events.